DSM-IV Axis II personality disorders and suicide and attempted suicide in China. (October 2016) - Tong, Yongsheng; Phillips, Michael R.; Conner, Kenneth R.
Abstract : Background: There are meagre data on Axis II personality disorders and suicidal behaviour in China. Aims: To describe the prevalence of Axis II personality disorders in suicides and suicide attempts in China and to estimate risk for these outcomes associated with personality disorders. Method: People who died by suicide ( n = 151), people who attempted suicide ( n = 118) and living community controls ( n = 140) were randomly sampled from four Chinese counties and studied using the Structured Clinical Interviews for DSM-IV-TR Axis I Disorders (SCID-I) and Axis II Personality Disorders (SCID-II). We also determined the prevalence of subthreshold versions of ten DSM-IV personality disorders. Results: Axis II personality disorders were present in 7% of the suicide group, 6% of the suicide attempt group and 1% of the control group. Threshold and subthreshold personality disorders had adjusted odds ratios (point estimates) in the range of 2.7–8.0 for suicide and for suicide attempts. Conclusions: Axis II personality disorders may confer increased risk for suicidal behaviour in China, but their low prevalence in the community and among people with suicidal behaviour suggests that other personality constructs such as select dimensional traits may be a more fruitful avenue for understanding and preventing suicide in China.